2018
DOI: 10.3390/ijms19061801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Macrophage Polarization in Inflammation during Infectious Diseases

Abstract: Experimental models have often been at the origin of immunological paradigms such as the M1/M2 dichotomy following macrophage polarization. However, this clear dichotomy in animal models is not as obvious in humans, and the separating line between M1-like and M2-like macrophages is rather represented by a continuum, where boundaries are still unclear. Indeed, human infectious diseases, are characterized by either a back and forth or often a mixed profile between the pro-inflammatory microenvironment (dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
811
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,034 publications
(895 citation statements)
references
References 84 publications
8
811
0
17
Order By: Relevance
“…Interestingly, CCL1 released from M2b cells is essentially required for maintaining the properties of M2b monocytes/macrophages . Growing evidences have shown that CCL1 is the specific molecular identifier of M2b and may serve as a marker for identifying M2b from the other subtypes of macrophages …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, CCL1 released from M2b cells is essentially required for maintaining the properties of M2b monocytes/macrophages . Growing evidences have shown that CCL1 is the specific molecular identifier of M2b and may serve as a marker for identifying M2b from the other subtypes of macrophages …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…Under normal physiologic conditions, monocytes in the blood retain a quiescent state (M0: CCL1 − , CD163 − , CD14 + ) . During infection, monocytes/macrophages acquire the M1 phenotype (IL‐10 − , IL‐12 + , iNOS + , CXCL9 + ), which is a major effector cells for the first line of host antibacterial defense . Mild burn injury (5% of the total body surface area [TBSA] burn) induces M1 macrophage polarization .…”
Section: M2b Macrophages and Diseasesmentioning
confidence: 99%
See 3 more Smart Citations